Determining the Moderating Role of Supervisory Support on the Relationship Between Organization Career Management and Employee Career Satisfaction: Evidence From Private Insurance Companies in Ghana - Korankye, Benard; Musah, Seidu; Adakwelu Ifeamalume, Okafor (International Journal of Scientific Research and Management (IJSRM), 2020)
The purpose of this study was to determine the moderating role of supervisory support on the relationship between organizational career management and career satisfaction of employees of selected five private insurance companies in Ghana. A survey method was used to collate information from 167 employees who work in the studied organizations through a simple random sampling approach. The descriptive, correlation, multiple regression, and the moderated multiple regression analysis were used to test the research hypothesis and their results showed three important findings: firstly, organizational career management positively and significantly correlates and had an impact on career satisfaction. Secondly, supervisory support positively and significantly correlates and had an impact on career satisfaction. Lastly, the moderating role of supervisory support was established to be positive and significant on the relationship between organizational career management and career satisfaction. The outcome contributes to the Job Demand Resource (JD-R) theory such that organizational career management and supervisory support could be employed as organizational resources to produce career satisfaction. The study suggests that more attention and commitment should be given to organizational career management and supervisory support by the management of the private insurance companies to promote the career satisfaction of their employees.